Pengembangan Media Pembelajaran Matematika Berbasis Android Pada Materi Transformasi Geometri Pada Siswa Kelas IX SMPN 15 Kota Kupang - Sonya Gale Bangngu; Juliana M. H. Nenohai; Damianus D. Samo (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2022)
The development of technology in the field of education is growing rapidly, thus requiring teachers to be more creative in developing technology-based learning media by utilizing android smartphones. Therefore, this study aims to develop and produce an Android-based mathematics learning media using smart apps creator on the material for geometry transformation for class IX of SMP Negeri 15 Kupang City that is valid, practical and effective. The method used in this research is the Research and method Development (R&D) and the models used in the development process this learning media is the ADDIE development model which consists of 5 stages, namely analysis (analysis), design (design), development (development), implementation (implementation) and evaluation (evaluation). The result showed that the learning media developed met the eligibility criteria that were valid, practical and effective. The average total validity by material experts is 4.5 and media experts is 4.3 with the â€œvery validâ€ category. The average total practicatility of the teacher was 4.71 and the students in the small group trial was 4.51, in the large group trial 4.43 with the â€œvery practicalâ€ category. The percentage of completeness in the small group trial obtained 100% results with the category â€œvery effectiveâ€ , in the large group trial the results obtained 82.14% with the category â€œvery effectiveâ€. So that android-based learning media is very feasible to use.